Effect of cyclic freezing on microstructure parameters of monoionic bentonites = Wpływ cyklicznego zamrażania na parametry mikrostruktury monojonowych bentonitów - Kozłowski, Tomasz; Grobelska, Edyta; Walaszczyk, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study the effects of cyclic freezing on microstructure of monomineral forms of bentonite were investigated. Samples of the non-frozen soil and the soil frozen were tested using scanning electron microscope SEM. The analysis of the photographs was conducted using Photo Shop CS4 software.
Keywords: betonit; bentonit z Chmielnika; zamrażanie; iły monojonowe; mikrostruktury; betonite; freeze-thaw; microstructure